Muscle strength, EEG biomarkers, and working memory as interacting predictors of cognitive function in cognitively impaired older adults - Song, Yagang; Jia, Shuqi; Wang, Xing; Wang, Aiwei; Li, Shufan; Ding, Feng; Ma, Tao; Wu, Xueping (Frontiers in Aging Neuroscience, 2025)
BackgroundCognitive decline in older adults is a pressing public health concern, with emerging evidence suggesting that both muscle strength and neural function may influence cognitive outcomes. However, the integrative mechanisms linking these domains remain insufficiently understood.ObjectiveThis study aimed to explore whether resting-state EEG characteristics and working memory mediate the relationship between muscle strength and global cognitive function in older adults with cognitive impairment. Methods: A cross-sectional study was conducted among 137 older adults (mean age = 72.65 ± 7.75) with cognitive impairment. Muscle strength was assessed using grip strength and 30 s chair stand tests. Resting-state EEG power across six frequency bands was recorded from 16 electrodes. Working memory was evaluated using a two-back task, and cognitive function was assessed via the MoCA. Mediation analyses were performed using the PROCESS macro (Model 4), controlling for age, sex, education, and BMI.ResultsGrip strength showed significant direct effects on cognitive function (β = 0.399, p < 0.001), with partial mediation by both working memory (β = 0.070, p < 0.05) and resting-state EEG (β = 0.150, p < 0.01). In contrast, lower limb strength was mediated only by working memory (β = 0.078, p < 0.05), while EEG-based mediation was not significant. The overall model explained 50.7% of the variance in cognitive outcomes.ConclusionThis study highlights the distinct mediating roles of working memory and EEG features in the muscle strength–cognition relationship. Grip strength, as a potential biomarker, may reflect central nervous system integrity and serve as a target for cognitive health interventions in aging populations.